2019
DOI: 10.1136/bmjopen-2018-026438
|View full text |Cite
|
Sign up to set email alerts
|

Exercise duRing Active Surveillance for prostatE cancer—the ERASE trial: a study protocol of a phase II randomised controlled trial

Abstract: IntroductionActive surveillance (AS) is the preferred primary treatment strategy for men with low-risk clinically localised prostate cancer (PCa); however, the majority of these men still receive radical treatment within 10 years due to disease progression and/or fear of cancer progression. Interventions designed to suppress tumour growth, mitigate fear of cancer progression and precondition men for impending radical treatments are an unmet clinical need. Exercise has been shown to delay the progression of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 99 publications
0
16
0
Order By: Relevance
“…Previous studies in the AS population have examined the effects of PA on QOL and psychological morbidity in combination with additional interventions (eg, diet, stress management, and behavioral support). 32,33 The findings from these studies demonstrated further improvements in physical and mental domains of QOL 32,33 and feelings of optimism 34 35,36 To our knowledge, the present study is the first to examine whether different levels of selfreported PA are associated with different QOL and EWB status from AS initiation until AS discontinuation or loss to follow-up.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies in the AS population have examined the effects of PA on QOL and psychological morbidity in combination with additional interventions (eg, diet, stress management, and behavioral support). 32,33 The findings from these studies demonstrated further improvements in physical and mental domains of QOL 32,33 and feelings of optimism 34 35,36 To our knowledge, the present study is the first to examine whether different levels of selfreported PA are associated with different QOL and EWB status from AS initiation until AS discontinuation or loss to follow-up.…”
Section: Discussionmentioning
confidence: 58%
“…Nonetheless, the supplemental interventions that were used (eg, diet, stress management, and behavioral support) preclude from drawing conclusions on the relationship between PA, QOL, and indices of psychological morbidity (eg, EWB) over time in men with low‐risk disease. In men on AS, the effect of certain types of PA (eg, exercise‐training) on psychological morbidity is currently being investigated by randomized controlled trials . To our knowledge, the present study is the first to examine whether different levels of self‐reported PA are associated with different QOL and EWB status from AS initiation until AS discontinuation or loss to follow‐up.…”
Section: Discussionmentioning
confidence: 96%
“…The exercise intervention has been described elsewhere. 8 In brief, the HIIT group was provided with a 12-week supervised aerobic HIIT program 3 times per week on a treadmill. Each exercise session consisted of a warm-up at 60% of peak oxygen consumption (VO 2peak ) for 5 minutes and high-intensity walking or jogging at a workload corresponding to 85% to 95% of baseline VO 2peak for 2 minutes, followed by active recovery at 40% of VO 2peak for 2 minutes, which was repeated 5 to 8 times.…”
Section: Interventionmentioning
confidence: 99%
“…In prostate cancer patients, for example, resistance exercise alone or combined with aerobic training has been shown to reduce postsurgical impairments from prostatectomy ( 3 ), reverse the array of adverse effects from androgen deprivation therapy (ADT) ( 4 11 ), and preserve physical function in those with bone metastases ( 12 ), in addition to improvements in quality of life ( 5 , 8 , 12 ). However, although the role of exercise medicine is being expanded to include low-grade cancer patients undergoing active surveillance ( 13 15 ), or high-grade patients to enhance tumor growth suppression ( 16 ) and survival ( 17 ), information regarding the actual exercise dose–response still needs to be determined ( 18 ).…”
mentioning
confidence: 99%